Research and application of unified cross-system data services for coal mines based on industrial internet platforms - WAN Maoquan; LI Hao; WANG Hao (Gong-kuang zidonghua)
Currently, the application of industrial internet platforms in coal mines faces issues such as the inability to fully utilize the value of data, limited data flow between different systems, and a lack of a unified permission management mechanism for cross-system data interactions. These issues increase the risks of data tampering and unauthorized access. A unified cross-system data service system for coal mines was proposed based on an industrial internet platform. The system comprised a five-layer cross-system data model (thematic domain grouping-thematic domain-business object-logical entity-attribute), which covered the monitoring and control level, production management level, and operation management level. It established an "Interface Layer-Service Layer-Storage Layer" collaborative architecture. The system integrated a dynamic protocol adaptation engine, containerized microservice deployment, and low-code interface configuration tools. Additionally, it employed a dynamic hierarchical authentication mechanism and an end-to-end behavior monitoring system. These features together enabled standardized access, secure transfer, and precise interaction of multi-source heterogeneous data. Test results showed that, compared to the traditional distributed interface model, the proposed system optimized average data response time from 270 ms to 148 ms and improved data processing accuracy to 99.57%. Practical application results indicated that over 12,000 hours of continuous operation, the service availability reached 99.6%, and data consistency errors were below 0.1%.